Affective and social pain modulation in children - Experimental evidence using picture viewing - Hillmer, Katrin; Kappesser, Judith; Hermann, Christiane; Justus Liebig University Giessen (My University, 2024)
Background: Children frequently encounter pain. Their pain like adults’ pain is probably modulated by social-affective factors. Despite its clinical relevance, such pain modulation has not been explored experimentally in children, and little is known about specific factors accounting for it such as catastrophizing. We examined pain modulating effects of pictures varying in social-affective content and personal meaning (e.g., mothers’ vs. strangers’ faces) using subjective and psychophysiological measures (skin conductance, heart rate, corrugator electromyography) as outcomes. Methods: Forty-two children (8–13 years) underwent tonic heat pain stimulation while viewing pictures (social-affective: their mothers’ faces with neutral expression, strangers’ neutral and happy faces; affective: positive and negative scenes). Furthermore, the contribution of children’s characteristics (e.g., anxiety, catastrophizing) and facets of the parent-child relationship to pain modulation was determined. Results: Viewing mothers’ faces or positive scenes reduced subjective pain intensity and corrugator activity in response to pain. Viewing happy strangers’ faces lowered corrugator activity. Enhanced pain experience due to negative affective stimuli was primarily observed psychophysiologically. The correlation between children’s tendency to catastrophize and pain relief by mothers’ faces was mediated by induced arousal, likely reflecting the degree of motivational activation of seeking social support. Conclusions: Pain relief by positive affective and social-affective stimuli extends previous findings in adults, especially regarding reduced pain-related facial muscle activity. Moreover, the results shed light on the interplay between catastrophizing and social context on children’s pain experience. Clinically, our results imply that just looking at pictures of their mothers (or positive scenes) might help to alleviate pain in children.
Keywords: ddc:150